BASIC PROPERTIES OF MINERAL OILS OF PETROLEUM ORIGIN (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This thesis provides information on quality requirements and basic physicochemical and performance properties such as demulsifying, anti-foaming and deaeration, chemical and thermal stability, sulfur content, acidity, purity, flash point, low temperature, viscosity index, lubricity and viscosity of diesel and energy petroleum oils.